Profile of the ability of prospective Biology teachers in making question instruments using Bloom's Taxonomy - Tengku Idris; Sepita Ferazona; Herlina Safitri (REID (Research and Evaluation in Education), 2021)
The purpose of this study is to determine students' ability to make Bloom's taxonomy questions. The study was conducted on students in the 5th semester of the 2020/2021 academic year who were taking evaluation courses and learning achievement techniques with a sample of 62 people. This research is a descriptive study using a checklist sheet as the main instrument that has been content validated by experts, questionnaires, and interviews as supporting data. Data were analyzed using the quantitative descriptive method. The results of the research show that students have very good abilities in making Bloom's taxonomy questions for the lower other thinking skills category with a percentage of 92.22% with details C1 100%, C2 95%, and C3 81.67%, while the students' ability in making questions with a higher level of other thinking skills is in the very poor category with a percentage of 44.17% with C4 54.17%, C5 46.67% and C6 31.17%. In addition, based on the form of questions, students' ability to design essay questions (74.17%) is better than multiple-choice questions (62.22%). The conclusion of this study is the ability of students to make questions based on Bloom's Taxonomy is in the fairly good category, with a percentage of 78.06%.